Accurate sequencing of DNA motifs able to form alternative (non-B) structures - Weissensteiner, Matthias H; Cremona, Marzia A; Guiblet, Wilfried M; Stoler, Nicholas; Harris, Robert S; Cechova, Monika; Eckert, Kristin A; Chiaromonte, Francesca; Huang, Yi-Fei; Makova, Kateryna D (Genome research, 2023)
Approximately 13% of the human genome at certain motifs have the potential to form noncanonical (non-B) DNA structures (e.g., G-quadruplexes, cruciforms, and Z-DNA), which regulate many cellular processes but also affect the activity of polymerases and helicases. Because sequencing technologies use these enzymes, they might possess increased errors at non-B structures. To evaluate this, we analyzed error rates, read depth, and base quality of Illumina, Pacific Biosciences (PacBio) HiFi, and Oxford Nanopore Technologies (ONT) sequencing at non-B motifs. All technologies showed altered sequencing success for most non-B motif types, although this could be owing to several factors, including structure formation, biased GC content, and the presence of homopolymers. Single-nucleotide mismatch errors had low biases in HiFi and ONT for all non-B motif types but were increased for G-quadruplexes and Z-DNA in all three technologies. Deletion errors were increased for all non-B types but Z-DNA in Illumina and HiFi, as well as only for G-quadruplexes in ONT. Insertion errors for non-B motifs were highly, moderately, and slightly elevated in Illumina, HiFi, and ONT, respectively. Additionally, we developed a probabilistic approach to determine the number of false positives at non-B motifs depending on sample size and variant frequency, and applied it to publicly available data sets (1000 Genomes, Simons Genome Diversity Project, and gnomAD). We conclude that elevated sequencing errors at non-B DNA motifs should be considered in low-read-depth studies (single-cell, ancient DNA, and pooled-sample population sequencing) and in scoring rare variants. Combining technologies should maximize sequencing accuracy in future studies of non-B DNA.
Keywords: nanopóry; vysoce účinné nukleotidové sekvenování; DNA, Z-Form; Sequence Analysis, DNA; Nanopores; DNA; zastoupení bazí; sekvenční analýza DNA; Nucleotide Motifs; High-Throughput Nucleotide Sequencing; Humans; lidé; Base Composition; nukleotidové motivy; Z-DNA